ANALISIS KESULITAN MAHASISWA DALAM PENGUASAAN KONSEP TURUNAN FUNGSI PADA MATA KULIAH KALKULUS - SULISTYANINGTYAS, ANNISA DWI; WANTIKA, RESTU RIA; RAHAYU, SRI; HADI, SUSILO (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2024)
Derivatives of functions are one of the teaching materials of the Calculus Course for the Electrical Engineering Study Program at PGRI Adi Buana University, Surabaya. This material is very important to study, especially for engineering students as a basis for mastering calculation concepts in subsequent courses. However, students still experience difficulties in mastering the concepts of the material and solving the questions given. The purpose of this research is to determine the level of difficulty students have in mastering the concept of derivative functions and to determine the causes of these difficulties. This research uses a descriptive qualitative method, where the researcher describes and explains in detail the problem of students' difficulties in studying derivatives of functions in the Calculus course. Data was taken from the results of the Quiz for students in the Electrical Engineering Study Program for the 2024/2025 academic year. The research results showed that 69% of students made Principle Errors (KP) and 32% made Calculation Errors (KH). So, it can be concluded that most students cannot remember existing rules, formulas or theorems and identify material concepts. Furthermore, it is hoped that the results of this research can be used as a basis for improving Calculus I learning, so that learning is more interesting and students are more enthusiastic in participating in the learning. ABSTRAKTurunan fungsi merupakan salah satu materi ajar dari Mata Kuliah Kalkulus bagi Program Studi Teknik Elektro di Universitas PGRI Adi Buana Surabaya. Materi tersebut sangat penting untuk dipelajari, khususnya bagi mahasiswa teknik sebagai dasar penguasaan konsep perhitungan di mata kuliah selanjutnya. Namun, mahasiswa masih merasakan kesulitan dalam penguasaan konsep materi dan penyelesaian soal yang diberikan. Tujuan penelitian ini adalah untuk mengetahui tingkat kesulitan mahasiswa dalam menguasai konsep turunan fungsi dan mengetahui penyebab dari kesulitan tersebut. Penelitian ini menggunakan metode kualitatif deskriptif, dimana peneliti menggambarkan dan menjelaskan secara rinci permasalahan kesulitan mahasiswa dalam mempelajari turunan fungsi pada Mata Kuliah Kalkulus. Data diambil dari hasil Quis mahasiswa Program Studi Teknik Elektro tahun akademik 2024/2025. Hasil penelitian menunjukkan bahwa 69% mahasiswa melakukan Kesalahan Prinsip (KP) dan 31% melakukan Kesalahan Hitung (KH). Sehingga dapat ditarik kesimpulan bahwa sebagian besar mahasiswa tidak dapat mengingat aturan, rumus, atau teorema yang ada dan mengidentifikasi konsep materi. Selanjutnya, hasil penelitian tersebut diharapkan dapat dijadikan dasar untuk perbaikan pembelajaran Kalkulus, sehinggan pembelajaran lebih menarik lagi dan mahasiswa lebih antusias dalam mengikutin pembelajaran tersebut.